Development Trends and Future of the Quantum Information Technology and Industry - Shuo Li; Xinxin Li; Xuesong Zhang; Fei Gao; Yuanzhen Chen; Siyuan Ren; Yichen Yu (中国工程科学)
The quantum information technology represents the frontier of international scientific and technological advancements, serving as a pivotal technological variable in the era of great changes and a strategic high ground for technological, and national power, competitions among major powers. This study reviews the strategic layouts and development trends of key directions in the field of quantum information abroad, as well as the current development status in China. By integrating these insights with national strategic needs, it analyzes the advantages and challenges faced by China in further developing quantum information science and technology and its related industries. Applying the thinking methodology of science and technology system engineering, and by investigating the research and development (R&D) of industrial technology applications and integrated innovation pathways, this study proposes, with a focus on quantum information technology forms, product forms, and industrial ecosystems, to systematically layout the development of the quantum information industry with quantum computing as a key driving force; to systematically deploy the quantum information industry chain by grasping the critical nodes of autonomy and controllability; to guide the R&D directions of national significant quantum engineering projects based on application scenarios; and to cultivate quantum information science and technology talents over a decade. These suggestions aim to provide insights and references for the development of China's quantum information industry.